Pendidikan Karakter Dalam Meningkatkan Kualitas Belajar Era Generasi Milenianl - Jamaludin As'ari; Nurus Sa’adah (Institut Agama Islam Sumatera Barat, 2023)
Abstract Etymologically, when traced from the origin of the word, the word character comes from the Latin